Mitochondrial Homeostasis in Acute Organ Failure - Stallons, L. Jay (2013)
The kidneys compose approximately 0.5% of the body mass but consume about 10% of the oxygen in cellular respiration. This discordance is due to the high energy demands on the kidney for reabsorption of filtered blood components and makes the kidney sensitive to mitochondrial stress, the primary source of cellular ATP. Regardless of the etiology, acute kidney injury (AKI) almost always involves aspects of mitochondrial dysfunction. Recent evidence from experimental models suggests that preserving mitochondrial function or promoting mitochondrial repair rescues renal function during AKI. In this review we discuss the effect of AKI on disruption of mitochondrial homeostasis, and how the dynamic processes of mitochondrial biogenesis, fission/fusion, and mitophagy influence renal injury and recovery.